2021
DOI: 10.15446/rev.colomb.quim.v50n1.90134
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas y aplicaciones reales del grafeno después de 16 años de su descubrimiento

Abstract: A 16 años del gran descubrimiento del grafeno los focos de atención vuelven a estar en este material con el reporte de su comportamiento superconductor dependiendo del apilado de sus capas. Sin embargo, su nombre durante estos últimos años no solo se ha relacionado a la superconductividad, sino que ha sido relacionado con una diversidad muy amplia de aplicaciones, en disciplinas muy diversas, entre las que cabe mencionar: materiales opto-electrónicos, electrodos para catálisis, dispositivos para tratamiento de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 384 publications
0
0
0
Order By: Relevance
“…Outra vantagem deste material bidimensional é a alta mobilidade dos portadores de carga, o que permite que o grafeno apresente uma fotodetecção muito rápida. Além disso, o grafeno é quimicamente inerte e robusto, pode manter sua integridade estrutural mesmo em altas temperaturas (acima de aproximadamente 500°C) e em valores de pH tanto baixo quanto alto em solução aquosa (Urcuyo et al, 2021). Outras características como impermeabilidade, alta transmissão de luz e baixo efeito Joule contribuem para aplicação em painéis solares (Vieira Segundo & Vilar, 2016).…”
Section: Propriedades Do Grafenounclassified
See 1 more Smart Citation
“…Outra vantagem deste material bidimensional é a alta mobilidade dos portadores de carga, o que permite que o grafeno apresente uma fotodetecção muito rápida. Além disso, o grafeno é quimicamente inerte e robusto, pode manter sua integridade estrutural mesmo em altas temperaturas (acima de aproximadamente 500°C) e em valores de pH tanto baixo quanto alto em solução aquosa (Urcuyo et al, 2021). Outras características como impermeabilidade, alta transmissão de luz e baixo efeito Joule contribuem para aplicação em painéis solares (Vieira Segundo & Vilar, 2016).…”
Section: Propriedades Do Grafenounclassified
“…No estudo realizado por Urcuyo et al (2021) foram descritas as principais aplicações do grafeno nas diversas áreas tecnológicas nos últimos 16 anos. De acordo com a pesquisa, esse material tem sido usado em conjunto com diversas tecnologias existentes de células solares, como as células de silício, orgânicas, heterojunções, poliméricas, sensibilizadas com corantes e de perovskitas, que, em sua maioria, estão em fase de testes para aplicação em escala comercial.…”
Section: Aplicações Do Grafeno Em Painéis Solaresunclassified
“…Since the discovery of graphene in 2004 and particularly in recent years, the number of scientific publications and patents has significantly increased, especially in the last five years (Lee et al, 2019). In general, graphene has been widely studied and reported as a two-dimensional material with intriguing physicochemical properties, including high thermal and electrical conductivity, large surface area, optical transparency, and mechanical strength, among others (Farías, Flores, Rosales, Sáenz, & López, 2017;Urcuyo Solórzano, Cordero Solano, & Gonzalez Flores, 2021). It has even been reported that graphene's strength is 200 times higher than structural steel, with hardness exceeding that of diamond (García, 2013;Pingale, Owhal, Katarkar, Belgamwar, & Rathore, 2021), in addition to its superior thermal and electrical properties compared to copper.…”
Section: Introductionmentioning
confidence: 99%
“…It has even been reported that graphene's strength is 200 times higher than structural steel, with hardness exceeding that of diamond (García, 2013;Pingale, Owhal, Katarkar, Belgamwar, & Rathore, 2021), in addition to its superior thermal and electrical properties compared to copper. Graphene has emerged as a highly attractive material for a wide range of applications across various fields, including technology, environment, medicine, and electronics, among others (Pachamango Bautista & Zapata Revoredo, 2018;Torkaman-Asadi & Kouchakzadeh, 2022;Urcuyo Solórzano et al, 2021). This enables the creation of products ranging from solid prosthetics for various body parts to extremely lightweight and exceptionally strong sports equipment.…”
Section: Introductionmentioning
confidence: 99%